Membangun Resiliensi Perempuan dalam Menghadapi Banjir di Sumatera Utara: Perspektif Kebijakan Responsif Gender - Juwita Siregar; Muhamad Fikri; Ika Arinia Indriyany (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Floods are one of the most frequent hydrometeorological disasters in Indonesia and cause various social, economic, and environmental impacts on communities. In disaster situations, women often face greater vulnerability than men due to limited access to resources, high domestic responsibilities, and minimal protection in disaster policies. Although the government has adopted a gender mainstreaming policy in development, its implementation in disaster management policies remains suboptimal. This study aims to analyze how flood management policies integrate gender perspectives and identify the impacts of floods on women. The study used a qualitative approach using literature study methods and media content analysis to understand the dynamics of policies and women's experiences in disaster situations. The results show that disaster management policies still tend to focus on technical and infrastructure aspects, while women's specific needs are often overlooked, particularly regarding security in refugee camps, access to reproductive health services, and increased domestic burdens during crises. This condition indicates that the integration of a gender perspective in disaster policies still faces various structural and institutional barriers. Therefore, efforts are needed to strengthen the implementation of gender-responsive policies so that disaster management does not only focus on physical mitigation, but is also able to provide fairer and more inclusive protection for all community groups.